Kreativitas di Industri Film dari Perspektif Faktor Ergonomi dan Kreativitas di ProduksiFilm Horor 'Pamali' - Chitra Lestari, S.I.Kom, M.I.Kom, Chitra Lestari, S.I.Kom, M.I.Kom (Profilm Jurnal Ilmiah Ilmu Perfilman dan Pertelevisian, 2024)
The combination of movies and video games allows for a more immersive entertainment experience and innovation. The entertainment industry has the ability to create works of art that are not only entertaining, but also provide interactive and learning experiences to the audience. It enables the creation of artwork that combines the strengths and appeal of both worlds, taking cinematography and the video game experience to a new level never seen before. During the production process of PAMALI Horror film, which is a fusion of game and film, ergonomic factors of the workplace are also very important. The study investigated how the ergonomic design of the workplace, including the unique filming locations, affected the creativity of the cast. Criteria such as efficiency, comfort, and safety of the workplace are discussed in. The ergonomic factor of the workplace is also very important, especially during the production process of the PAMALI Horror film, which is a blend of game and film. The study investigated how the creativity of the performers was influenced by the ergonomic design of the workplace, including unique filming locations. Factors such as comfort, safety, and efficiency of the workspace are discussed with respect to artistic expression and the level of creativity that can be achieved by the performers in the environment. The focus of theresearch is issues related to increasing the creativity of filmmakers during the film and game production process, as well as the ergonomic impact of the process. This research is included in the type of literature research, which is research whose objects are books as data sources. The aim of this study was to uncover the relationship between ergonomic design of workplaces and levels of creativity in the process of making horror films. In practical terms, the findings could help the film industry improve workplace designs that support the creative expression and well-being of performers, even in challenging locations like helicopter crashes